Dampak Pelatihan Kepemimpinan Transformasi Untuk Memperkuat Engagement Karyawan CV BM di Sentolo Yogyakarta - Raspan Hamdi; Kamsih Astuti (Jurnal Psikologi, 2022)
This study aims to determine the effect of transformational leadership training on work engagement of CV BM employees. The hypothesis proposed is that there are differences in the level of employee work engagement before transformational leadership training at leaders and after transformational leadership training at leaders where employee work engagement scores are higher after providing transformational leadership training interventions to leaders. The subjects in this study were 32 employees of CV BM company and leaders as the experimental group. The design used is one group pre-test and post-test. The results of the Paired Sample T-Test show that the pretest and posttest scores for employees obtained the value of t = -4.989 p (0.01), which means there are differences in work engagement scores between pretest and posttest, where the posttest score is greater than the pretest score . This shows that transformational leadership training given to leaders affects the increase in employee engagement work at CV BM Yogyakarta.